2015
DOI: 10.9734/jsrr/2015/13692
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fertility and Crop Yield Variability under Major Soil and Water Conservation Technologies in the Usambara Mountains, Tanzania

Abstract: Indigenous soil and water conservation (SWC) technologies such as miraba (rectangular grass strip bounds that do not necessarily follow contours) and micro ridges have been used widely in the Usambara Mountains, Tanzania. However, their strengths and limitations to crop productivity have not been investigated. This study aimed to determine soil fertility and crop yield variability under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
2
1
0
Order By: Relevance
“…Exchangeable potassium is significantly at (p < 0.01) and negatively (r = -0.431) correlated with bulk density. The results of this study is consistent with the finding of Mwango et al (2015) who reported that, a significant correlation between phosphorus and soil pH was observed.…”
Section: Available Phosphorus (Avp Mg/kg) and Exchangeable Potassium supporting
confidence: 93%
See 2 more Smart Citations
“…Exchangeable potassium is significantly at (p < 0.01) and negatively (r = -0.431) correlated with bulk density. The results of this study is consistent with the finding of Mwango et al (2015) who reported that, a significant correlation between phosphorus and soil pH was observed.…”
Section: Available Phosphorus (Avp Mg/kg) and Exchangeable Potassium supporting
confidence: 93%
“…However, negatively correlated with bulk density (r = -0.201) and (r = -0.304) sand and the correlation is not significant in both case at (p < 0.01 and 0.05. The result is in line with that of Mwango et al (2015) who reported that total nitrogen was significantly correlated with OC and phosphorus (p<.001).…”
Section: Total Nitrogen (Tot N%)supporting
confidence: 92%
See 1 more Smart Citation